(untitled) (Applied Biological Research, 2023)
Isocyanates (ICN) have drawn considerable attention in recent past as they can react with a variety of nucleophiles including DNA, proteins and cause damage(s). However, pathophysiological implications resulting from the occupational and accidental exposures of ICN are yet too elusive. It may be produced in high concentrations in the conditions of chronic renal failure and chronic inflammatory diseases (diabetes mellitus, rheumatoid arthritis, etc.). In this study, mammalian dsDNA was modified with ICN and characterized by UV, fluorescence, FT-IR and thermal melting methods. ICN mainly reacts with exocyclic nitrogen of DNA bases. Antibodies against carbamylated-DNA were raised in rabbits and characterized by direct binding and inhibition ELISA. The presence of anti-carbamylated-DNA autoantibodies in the sera of diabetic nephro pathy patients was evaluated by ELISA. Carbamylated-DNA exhibited hyperchromicity at 260 nm and depicted increase in ethidium bromide assisted fluorescence as compared to the native DNA. Furthermore, the appearance of prominent new peaks in FT-IR profile at different wave numbers suggested carbamoylation-induced changes in the vibration of sugar-phosphate backbone, base(s) etc. Carbamylated-DNA was highly immunogenic as compared to the native DNA. Experimental induction of antibodies against carbamylated-DNAand presence of autoantibodies against carbamylated-DNA in the sera of diabetic nephropathic patients point towards the significance of carbamylated-DNA in diabetic nephropathy.